A20 Haploinsufficiency in East Asia - Kadowaki, Tomonori; Kadowaki, Saori; Ohnishi, Hidenori (Frontiers in Immunology, 2021)
A20, encoded by the TNFAIP3 gene, is a negative regulator of tumor necrosis factor (TNF)-nuclear factor-κB signaling. It was recently demonstrated that A20 haploinsufficiency (HA20), caused by a heterozygous mutation in the TNFAIP3 gene, can present as an early onset autoinflammatory disease resembling Behçet’s disease (BD). In addition to autoinflammatory symptoms, HA20 was also reported to be associated with autoimmune diseases and immunodeficiency. Because the phenotypes associated with HA20 are broad, with different severities observed even among individuals in the same family with identical mutations, it has been assumed that the symptoms of HA20 may depend on genetic background and environmental factors. In this review, we summarize the characteristics of patients with HA20 in East Asia and compare these with patients in other regions, mainly the USA and Europe. Patients with HA20 in East Asia developed recurrent fever more frequently than patients in other regions, but were less likely to develop typical BD symptoms such as skin rashes and genital ulcers. In addition, patients with HA20 in East Asia had low rates of complication with autoimmune diseases and low autoantibody detection rates. While anti-TNF-α agents were the primary treatments for severe HA20 in East Asia, anti-interleukin-1 agents and Janus kinase inhibitors were also administered in other regions. Future studies will need to establish methods for analyzing the pathophysiology of HA20 and determining optimal treatment strategies for each patient.